A promoção da educação ambiental a partir da problemática dos resíduos sólidos: uma abordagem lúdica. - RAMOS, Ana Caroline David (Universidade Federal do Pará, 2024)
Faced with the complex environmental context that we experience today, this study proposes to highlight the problem of solid waste in the school environment, considering that basic education institutions are configured as a space for the community, for cognitive and social development, responsible for the formation of their students, and the environment is conducive to the dissemination of awareness for the preservation of the environment. That said, the present research seeks to promote environmental education through the construction of ludic pedagogical teaching material, starting from the problem of urban solid waste. The target audience will be students from the 5th year of Elementary School at the Rotary Municipal School, located in the Condor neighborhood, on the outskirts of Belém-Pa. The aim is, with the applied methodology, to instigate the interest of the students in the issue, to build a competition that can approach the theme in a playful and productive way and, finally. To elaborate an educational product (game script) that can disseminate the proposal to other Institutions.